2019
DOI: 10.2207/qjjws.37.200
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Standardizing for Evaluation Method of Transverse Varestraint Test

Abstract: 1. 緒 言 溶接時の高温割れ発生防止には,割れ発生時の温度やひ ずみなど普遍な物理量を用いた設計段階からの予測が重要 となる.高温割れ感受性評価では,これまでにバレストレ イン試験 1,2) や,C 形ジグ拘束突合せ割れ試験 3) ,Houldcroft 試験 4-6) ,Fissure bend 試験 7,8) などが提案,規格化され,評価 試験に用いられてきた.中でもバレストレイン試験は,こ れまでに最も広く用いられてきた高温割れ感受性評価試験 である. 本試験は,溶接(一般的には TIG メルトラン溶接が用い られる)中の試験片表面に強制的に曲げひずみを加えるこ とで高温割れを発生する外部負荷式の試験方法である.ひ ずみ負荷の方向に応じて,溶接方向と平行に曲げるロンジ 式,垂直に曲げるトランス式,熱源を移動せずに曲げるス ポット式の各試験が実施され,両曲げ式と片曲げ式の試験 機が使用されている.ロンジ式やスポット式は溶接熱影響 部の液化割れや延性低下割れ,トランス式は溶接金属部の 凝固割れ(延性低下割れに利用される場合もある)の評価 にそれぞれ適用されている.試験によって発生した割れの 数や長さを測定し,割… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The nominal strain generated by the bending can be calculated from the specimen thickness and the radius of the bending block. However, it has been reported that in this test, the estimated nominal strain and the actual strain acting on the weld metal differ significantly due to localized heat 3,4) .…”
Section: Introductionmentioning
confidence: 67%
“…The nominal strain generated by the bending can be calculated from the specimen thickness and the radius of the bending block. However, it has been reported that in this test, the estimated nominal strain and the actual strain acting on the weld metal differ significantly due to localized heat 3,4) .…”
Section: Introductionmentioning
confidence: 67%